2015
DOI: 10.1016/j.sbspro.2015.04.387
|View full text |Cite
|
Sign up to set email alerts
|

Adults’ Education and Agricultural Innovation: A Social Learning Approach

Abstract: Social learning processes can be the basis of a method of agricultural innovation that involves expert and empirical knowledge. In this sense, the objective of this study was to determine the effectiveness and sustainability of an innovation process, understood as social learning, in a group of small farmers in the southern highlands of Peru. Innovative proposals and its permanence three years after the process finished were evaluated. It was observed that innovation processes generated are maintained over tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…While it has been found that farmers' adoption of practices is influenced by production yields and costs (TerAvest, Carpenter-Boggs, Thierfelder, & Reganold, 2015), a review of the literature shows that adoption of agroecological practices depends not only on the innovations and practices presented, but also on the social networks that support the implementation of those innovations and behavior changes (Kroma, 2006). Adults have accumulated knowledge and experience that they apply to the learning process (Kroma, 2006), constantly reflecting and rethinking as part of learning and decision making (Barrantes & Yagüe, 2015). Social learning brings together knowledge through relationships and interactions with others over time (Flora, 1998).…”
Section: Farm Incubator Program Models and Adult Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…While it has been found that farmers' adoption of practices is influenced by production yields and costs (TerAvest, Carpenter-Boggs, Thierfelder, & Reganold, 2015), a review of the literature shows that adoption of agroecological practices depends not only on the innovations and practices presented, but also on the social networks that support the implementation of those innovations and behavior changes (Kroma, 2006). Adults have accumulated knowledge and experience that they apply to the learning process (Kroma, 2006), constantly reflecting and rethinking as part of learning and decision making (Barrantes & Yagüe, 2015). Social learning brings together knowledge through relationships and interactions with others over time (Flora, 1998).…”
Section: Farm Incubator Program Models and Adult Learningmentioning
confidence: 99%
“…Additionally, agroecology is, at its roots, a participatory and action-oriented approach that recognizes farmers' own knowledge and expertise in understanding the complexities of ecosystem interactions (Gliessman, 2014;Méndez et al, 2013;Wezel et al, 2009). Through this lens, hands-on participatory methods that facilitate an environment where farmers can experiment, and then relate those experiences within a social network, can lead to learning and innovations in agroecological resource management (Barrantes & Yagüe, 2015;Hassanein & Kloppenburg, 1995;Kroma, 2006). This is especially important for participant groups with a diversity of educational experiences, as hands-on learning through field programming has been shown as an effective educational strategy accessible to all, even those with limited or low levels of formal education (Davis et al, 2012).…”
Section: Farm Incubator Program Models and Adult Learningmentioning
confidence: 99%
“…Esa ambigüedad en la definición conlleva a que varios procesos sean reportados como estudios de caso exitosos de innovación social aunque carezcan de algún grado de innovación (Arias Pérez & Aristizábal Botero, 2011). Además de ello, la literatura reciente evidencia ciertos vínculos entre innovación social, ciencias naturales e ingeniería; ejemplo de ello son los lineamientos del programa Horizon2020 de la Unión Europea (Koczinszky & Somosi, 2016) o las diversas experiencias que demuestran que muchas de las nuevas tecnologías en el campo rural no lograron producir resultados esperados debido a la falta de interés por parte de los agricultores, poca flexibilidad para adaptarse a las necesidades personales o por falta de proactividad (Barrantes & Yagüe, 2015).…”
Section: Introductionunclassified
“…El aprendizaje es el proceso en el cual un individuo adquiere conocimientos [1]- [3], habilidades [4], [5] y actitudes [1], [4] a partir de enseñanza directa (generada por experiencias personales) o indirecta (transmitida por otro individuo) en el tiempo; la medición del aprendizaje consiste en el desarrollo de herramientas que permitan definir cuantitativa y cualitativamente la cantidad de información que el usuario efectivamente adaptó en su razonamiento [4], [5]. Uno de los aspectos de mayor inferencia en el aprendizaje y su evaluación es la edad [5], [17] al inferir en cambios en la capacidad de asimilar conceptos por parte de un individuo; factores como la receptibilidad neurológica, capacidad de asimilación, conciencia de entendimiento y capacidad de retención [6], [18].…”
Section: Introductionunclassified